ВЛИЯНИЕ ПРАЙМИНГА НА АКТИВНОСТЬ АНТИОКСИДАНТНЫХ ФЕРМЕНТОВ (СУПЕРОКСИДДИСМУТАЗА И ПЕРОКСИДАЗА) КУКУРУЗЫ С ПРИЗНАКОМ ЦМС ПРИ РАЗЛИЧНОМ ЗАСОЛЕНИИ (Experimental biology, 2009)
It was studied the influence of seeds priming by biologically active preparations from biohumus on functional activity of superoxidedismutase and peroxdase in leaves and roots of 10-days sprouts of maize with the Bolivian type of the cytoplasmic male sterility, which grown up at various concentration NaCl.
Keywords: concentration NaCl.; biologically active